FEEDING OF CLAWED CRAYFISH BY THE ROOT PLANT BIOMASS OF THE HIGHER PLANTS AS A MONO-DIET - Пальчик, О. А.; Дехтярева, Е. А.; Панчишный, М. А. (Scientific Progress & Innovations, 2013)
The article contains results of trial testing fodder for crustaceans in the form of the root biomass of higher terrestrial plants as a mono-diet. Test results indicate that the feeding of root biomass of higher terrestrial plants is more efficient than the mixed type of food. Among the studied variants the best biometrics of crayfish was recorded during feeding by the root mass of lettuce. The study has found that when you place in an aquarium the root of higher plants, the chemical properties of water are gradually improving, that is, terrestrial higher plants as well as water can purify the water.